Protein-sparing ability of carbohydrates from different sources in diets for fry of stinging catfish Heteropneustes fossilis - Rahman, Mohammad Lutfar; Salam, Mohammad Abdus; Ahsan, Md Emranul; Hossain, Md Shakhawate; Hossain, Md Arman (Penerbit Universiti Kebangsaan Malaysia, 2017)
The experiments were carried out to evaluate the protein-sparing effect in Heteropneustes fossilis fry (0.751 ± 0.01 g) fed for 90 days with six isocaloric diets containing 45, 40 or 35% of casein-protein and 25, 30 or 35% of glucose/dextrin, combined properly as the work purpose. The highest weight gain was recorded in fry fed with 35% dextrin and 35% crude protein level. Interestingly, the value of SGR (2.950±0.017) and PER (1.793±0.03) were significantly (p<0.05) increased with reducing protein level from 45 to 35% and with increasing carbohydrate level from 25% to 35%, respectively. However, the poorest growth was recorded in the fry fed with glucose containing diets than dextrin-containing diets. Protein deposition was significantly (p<0.05) lower in fry fed with the glucose diets at the protein level of 45% than those fed with 40 or 35%, indicating that H. fossilis utilize dextrin easily than glucose. Increase of dextrin content from 35 to 45% did not reduce (p<0.05) the weight gain, even reducing the dietary protein from 45 to 35%. This fact suggests that carbohydrate spare protein by using dextrin as energy source.